Positive solutions for Sturm-Liouville boundary value problems in a Banach space - Su, H.; Liu, L.; Wu, Yong Hong (Hindawi Publishing Corporation, 2012)
We consider the existence of single and multiple positive solutions for a second-order Sturm-Liouville boundary value problem in a Banach space. The sufficient condition for the existence of positive solution is obtained by the fixed point theorem of strict set contraction operators in the frame of the ODE technique. Our results significantly extend and improve many known results including singular and nonsingular cases.